Estimation of co-channel signals with linear complexity. - Miller, C.L.
To increase wireless system capacity using co-channel signals and multiple receiver antennas, we develop the partitioned Viterbi algorithm (PVA). The PVA estimation complexity increases linearly with each additional co-channel signal rather than exponentially as it does with joint maximum-likelihood sequence estimation (MLSE). The estimation problem involves multiple signals simultaneously transmitted and observed through slow-fading, frequency-selective channels. Although transmission is assumed to be in bursts according to a time-division multiple-access scheme, more than one signal can occupy the same time and frequency slot (these signals are referred to as ?co-channel? signals). Separation and estimation of the symbol bursts is accomplished by exploiting channel differences, PVA estimation consists of a set of Viterbi detectors, one per signal, that operate in parallel with cross-coupling to allow approximate interference cancellation by means of tentative decisions. The forward filter of a decision feedback equalizer (DFE) is used to ?prefilter? received signals prior to PVA estimation. Prefiltering delays the energy of interfering signals so that tentative decisions become reliable enough to use. Simulation results show PVA performance remains near-optimal with respect to the performance of joint MLSE
Keywords: DFE prefilter; MIMO algorithm; PVA estimation; Viterbi detectors; Antenna diversity; Approximate interference cancellation; Bursts transmission; Co-channel interference; Co-channel signals estimation; Computational complexity; Decision feedback equalizer; Forward filter; Frequency-selective channels; Interfering signals; Joint MLSE; Least squares channel estimation; Linear complexity; Maximum-likelihood sequence estimation; Multiple receiver antennas; Multiple signals estimation; Partitioned Viterbi algorithm; Simulation results; Slow-fading channels; Symbol bursts estimation; Symbol bursts separation; Tentative decisions; Time-division multiple-access.; Wireless system capacity